Educational Values in Mepajar Tradition of Kedongan Village, Kuta, Badung: Ethnopedagogics Literature - Rasna, I Wayan; Widyantara, I Made Sugi (Jurnal Pendidikan dan Pengajaran, 2022)
In Bali, Balinese dancing have become a tradition that has existed since a long time ago. Mepajar is a sacred activity that involves Balinese dancing such as Sandar Gede, Sandar Cenik, Rangda, dan Barong. The aims of this research were, 1) to describe how the process of implementing the Mepajar tradition in the Kedonganan traditional village and 2) to describe what educational values are included in the Mepajar tradition in the Kedonganan traditional village. The research was qualitative research. The conclusion of this research is the Mepajar tradition in the Kedonganan traditional village begins with the emergence of the Sandar Cenik dance, Sandar Gede followed by the Barong Ket, Rarung and Rangda dance performances and it takes about three hours. The Mepajar tradition in the Kedonganan traditional village has three educational values, i.e. religious education value, moral education value, and social education value.